1998
DOI: 10.1097/00007890-199812270-00008
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Randomized Trial of Mycophenolate Mofetil With Neoral or Tacrolimus After Orthotopic Liver Transplantation1,2

Abstract: The use of Mycophenolate Mofetil with N or FK and an identical steroid taper after orthotopic liver transplantation is associated with excellent graft and patient survival, and at 6 months, only 191% of the patients experienced rejection, with a 48% overall infection rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(50 citation statements)
references
References 16 publications
3
45
0
2
Order By: Relevance
“…Another study also confirmed that allograft rejection is linked to the indirect pathway of allorecognition (36). MMF has been shown to attenuate chronic rejection of transplants in rats and humans (37)(38)(39). In addition, graft rejection by DTH-like reactions by Th1 cells has been inferred as playing a role in chronic rejection (1,40).…”
Section: Discussionmentioning
confidence: 78%
“…Another study also confirmed that allograft rejection is linked to the indirect pathway of allorecognition (36). MMF has been shown to attenuate chronic rejection of transplants in rats and humans (37)(38)(39). In addition, graft rejection by DTH-like reactions by Th1 cells has been inferred as playing a role in chronic rejection (1,40).…”
Section: Discussionmentioning
confidence: 78%
“…These factors that limit the ability to use MMF are not usually seen in kidney transplant patients and explain the differences in dropout rates. Fisher et al reported in their randomized trial of MMF with Neoral versus TAC, that gastrointestinal toxicity and bone marrow suppression were not notable, although the study was limited to a 6-month follow-up, and target dose of MMF at 6 month was 1 g/day (24). This study was not designed to evaluate steroid withdrawal after L Tx, although there appeared to be a slightly higher number of patients in the MMF group that were steroid free.…”
Section: Hematologymentioning
confidence: 96%
“…[4][5][6][7] In addition, recent studies of liver transplant recipients suggest that MMF may prevent acute rejection in patients who are unable to tolerate calcineurin inhibitors and may be effective in treating unresponsive episode hepatic allograft rejection. [8][9][10] Patient and graft survival rates at 1 year after liver transplantation continue to improve and presently are approaching 85% and 80% at major liver transplant centers in the United States, respectively. Despite these encouraging results, recent reports noted that acute hepatic allograft rejection still occurs in up to 40% to 50% of liver transplant recipients.…”
mentioning
confidence: 99%